2002
DOI: 10.1034/j.1399-6576.2002.460410.x
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided central venous cannulation in infants and children

Abstract: The ultrasound-guided technique for placement of central venous catheters was easy to apply in infants and children. It is our impression that it increased the precision and safety of the procedure in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
3

Year Published

2003
2003
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 8 publications
2
54
1
3
Order By: Relevance
“…Although the authors found that the overall success rate for US-guided catheterisation was higher than that for AL-based catheterisation (94.7% vs. 75.9%), no difference was found between the two methods for patients aged below one year and for patients who weighed less than 10 kg. (27) Asheim et al's study, (28) which involved 42 paediatric patients aged 0-177 months and weighing 3-45 kg, reported a 100% success rate in US-guided CVCs (95% at the first attempt) and no complications. Denys et al (20) also reported a 100% success rate in US-guided CVCs (78% at the first attempt).…”
Section: Discussionmentioning
confidence: 99%
“…Although the authors found that the overall success rate for US-guided catheterisation was higher than that for AL-based catheterisation (94.7% vs. 75.9%), no difference was found between the two methods for patients aged below one year and for patients who weighed less than 10 kg. (27) Asheim et al's study, (28) which involved 42 paediatric patients aged 0-177 months and weighing 3-45 kg, reported a 100% success rate in US-guided CVCs (95% at the first attempt) and no complications. Denys et al (20) also reported a 100% success rate in US-guided CVCs (78% at the first attempt).…”
Section: Discussionmentioning
confidence: 99%
“…Die Punktion der VJI unter sonographischer Bildgebung ist eine Methode, die die Erfolgsquote der zentralvenösen Kanülierung deutlich steigert [1,3,8,19]. Die Darstellung des Gefäßquerschnitts und seiner unmittelbaren Umgebung erlaubt ein weit gehend kontrolliertes Vorschieben der Kanüle und erhöht die Trefferwahrscheinlichkeit vermutlich auch dann, wenn auf eine Kopftieflagerung des Patienten und eine Beatmung mit PEEP verzichtet wird.…”
Section: R Larsen Homburg/saarunclassified
“…Fehl-bzw.Mehrfachpunktionen sind aber häufig Ursache oder Wegbereiter von Komplikationen, die durch eine unzureichende Venenfüllung, die anatomischen Verlaufs-oder Durchmesservarianten und thrombotisch bedingte Wandveränderungen nach stattgehabter Kanü-lierung begünstigt werden [1,2,3,7]. Komplikationen,wie die akzidentelle Karotispunktion oder ein Pneumothorax, Nervenläsionen oder eine extradurale Kanülenposition,sollen mit einer Häufig-keit von 8-25% auftreten [5,10,13,18,19].…”
Section: Diskussionunclassified
See 1 more Smart Citation
“…Nevertheless, early it was manifest that the use of US lead to an increased rate of successful insertion (both on the whole and at the initial try), quicker cannulation and a reduced rate of insertion-related adverse events [102,105,106] . In recent years, several studies [100][101][102][107][108][109][110] and meta-analyses [38,105,111] compared the "blind" approach to US-guided approach in pediatric patients and stated that the latter is much more effective and safe. According to the guidelines recommendations, US-guided catheter insertion is recommend as the primary method and not as a subsequent choice or a "salvage" technique in case of failure [99] .…”
Section: Neonates Infants Childrenmentioning
confidence: 99%